Treatment with lenalidomide and dexamethasone in patients with multiple myeloma and renal impairment - Dimopoulos, M.A.; Terpos, E.; Goldschmidt, H.; Alegre, A.; Mark, T.; Niesvizky, R. (Cancer Treatment Reviews, 2012)
Renal impairment (RI) is a common complication affecting patients with multiple myeloma (MM). Timely identification of MM-related RI and early treatment with novel antimyeloma agents can reverse renal damage in a high proportion of patients and improve outcomes. The IMiDs® immunomodulatory compound lenalidomide (Len) in combination with dexamethasone (Dex) is an effective and well-tolerated regimen for patients with relapsed or refractory (RR) MM. A retrospective analysis of Phase III data has shown that Len/Dex remains effective and well-tolerated in patients with moderate or severe RI, albeit with an increase in myelosuppression. This analysis demonstrated that in a high proportion of patients Len/Dex treatment can reverse MM-related RI and restore normal function. Lenalidomide has a predominantly renal route of excretion and in patients with RI the plasma concentration and half-life of the drug are significantly increased. As a consequence, lower starting doses are required in patients with RI to avoid over-exposure and an increased risk of adverse events, while maintaining good therapeutic index. A prospective cohort study in 50 patients with RRMM has reported that when Len/Dex dosing was adjusted according to renal function, response rates and survival outcomes were similar in patients with and without RI, and there was no increase in adverse events in patients with RI. Further clinical studies are required to confirm the efficacy and tolerability of Len/Dex regimens in MM patients with RI, and to evaluate the impact of reversing renal damage in terms of patient survival. © 2012 Elsevier Ltd.
Keywords: Dosing; Efficacy; Lenalidomide; multiple myeloma; renal impairment; safety